XPC is an RNA polymerase II cofactor recruiting ATAC to promoters by interacting with E2F1 - B. Bidon (Nature Portfolio, 2018)
XPC plays an important role in the nuclear exicision repair pathways. Here the authors show that in addition, XPC plays a role in transcription regulation by interacting with KAT2A and E2F1 and recruiting the ATAC coactivator complex to promoters.